Phenotypic and molecular characteristics of Francisella tularensis leading to enhanced surveillance tools - Molins Schneekloth, Claudia Roser, author; Belisle, John T., advisor; Schweizer, Herbert P., advisor; Petersen, Jeannine M., committee member; Reardon, Kenneth F., committee member (Colorado State University. Libraries, 2007)
Francisella tularensis is divided into four subspecies (tularensis, holarctica, mediasiatica, and novicida), of which two, tularensis (type A) and holarctica (type B), are clinically relevant as the etiologic agents of tularemia. The bioterrorist attacks of 2001 and this bacterium's high infectivity prompted increased research funding for F. tularensis with specific emphasis on therapeutics, diagnostics, and vaccines for tularemia. The focus of the work presented in this dissertation is the development of tools for enhancing the identification of F. tularensis within clinical and environmental samples. The observation that F. tularensis is inhibited when co-plated with Escherichia coli led to the hypothesis that the inhibitory substance could be of use as a diagnostic reagent. Using genetic methods, the inhibitory substance was identified as aerobactin. Given aerobactin's lack of specificity for Francisella, its use as a diagnostic reagent was reconsidered and the focus of these findings shifted to understand the significance of this iron chelating molecule in relation to the survival of F. tularensis in the presence of siderophore-producing bacteria. Separate from the above studies, epidemiological and molecular analyses provided evidence for subpopulations (A.I and A.II) of the highly virulent F. tularensis subsp. type A and that these subpopulations differed in their resulting clinical manifestations, geographical location, and preferential vectors. Based on these studies, we hypothesized that that genomic differences exist between A.I and A.II subpopulations and can be used to develop a diagnostic assay for differentiation of A.I and A.II. Additionally, it is possible that the genomic differences will lead to identification of virulence factors linked to the differential disease outcome associated with infections caused by the two subpopulations. Two PCR assays, one to identify subpopulations A.I and A.II as well as to discriminate from F. tularensis subspp. type B and novicida and another specific for subpopulation A.I, were developed based on genomic regions of difference identified by genomic suppression subtractive hybridization. In all, 18 genomic regions of difference were identified and verified among a panel of characterized F. tularensis subsp. type A isolates. Bioinformatic analyses revealed that genomic differences occurred in genes encoding hypothetical proteins, previously described proteins, and within intergenic regions. In silico analyses also identified products that could be associated with the differential clinical outcomes associated with these two F. tularensis subsp. type A subpopulations. This dissertation defines phenotypic and molecular characteristics of F. tularensis that provide new tools for improving the ability to identify and survey F. tularensis both within clinical samples and in the environment.
Keywords: microbiology